TESTAMENT OF PETER I – TO IDENTIFY THE INITIATOR OF THE FORGED DOCUMENT - Natsvaladze , Mamuka (Collection of scientific papers «ΛΌГOΣ», 2022)
Testament of Peter I became an outstanding bestseller among the world political documents since it was published in the 10-ies of the XIX century. It reflected the fundamental trends and directions of the Russian imperial policy thoroughly. Therefore, it was used as an instrument of the ideological fight against the Russian Empire and then against its successor — the Soviet Union by the western countries. In addition to ideological disputes, the forged testament of Peter I attracted attention from a scientific point of view. The question was to identify the party interested in creating such a forged document, as well as the date and purpose of creation. A completely different version unlike the previous ones has been established by the current research. In particular, the initiator of the falsification of Peter I’s testament was the King of Prussia Frederick II. The aforementioned initiative arose during the Seven Years’ War in the 60-ies of XVIII century, after the development of the rudimentary version of the Greek Project by Prussia and Russia, when Frederick II had to hide his authorship of the Greek Project for his own security and the security of the country as well.